Low accuracy of identifying Neotropical deer species by scat morphology. (2nd January 2017) - Costa, Eugênia Barbosa Varella; de Oliveira, Márcio Leite; Peres, Pedro Henrique de Faria; Grotta-Neto, Francisco; Vogliotti, Alexandre; Piovezan, Ubiratan; Duarte, José Maurício Barbanti
ABSTRACT: Morphometric feces data are used to identify ungulates, but their effectiveness is questioned by numerous authors. Herein, we evaluated the efficiency of this tool in discriminating scat samples from Neotropical deer with sympatric distributions. We performed discriminant analysis of previously identified scat samples ( n  = 204). The accuracy of discriminant analysis (56–92%) was lower than the confidence limit established in this study in all sympatric combinations expected in these biomes. These results demonstrate serious limitations regarding the use of scat morphometry for species identification of Neotropical deer and reinforce the need to use non-invasive genetic techniques.